Honorarji prvega slovenskega poklicnega pisatelja - Kočnik, Neža (Jezik in slovstvo, 2020)
The article presents a systematic overview of Ivan Cankar's royalty payments with regard to the relationships he built with publishers and editors. While the main source of information about the book editions was Cankar's own correspondence, the information about publications in periodicals originates from his editors' balance sheets and other records. Lavoslav Schwentner represents the main publisher, followed by Ottomar Bamberg, Fran Levec, Fran S. Finžgar and Valentin Podgorec. The editors responsible for royalty payments from periodical publications are presented chronologically, that is, according to the period during which they held the editorial position. In the given table, the royalties Cankar collected from the book editions of his works are presented alongside the retail prices of the books at the time of publication. In addition to the writer receiving high royalty payments for both book editions and periodical editions, he frequently used his confidence and rhetorical skills to persuade publishers and editors to pay out advances, which he was often unable repay.
Keywords: book-publishing royalties; Cankar, Ivan; honorarji; Slovenian writers; slovenski pisatelji